Peningkatan Kemampuan Gerak Passing dalam Permainan Sepak Bola Melalui Pendekatan Teams Games Turnament - Ahmad Ainur Rofiq; Muhammad Bambang Herinanta; Mochamad Ridwan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study seeks to enhance passing abilities in football among students of class X TAV 2 at SMK Negeri 3 Surabaya by applying the cooperative learning model known as Teams Games Tournament (TGT). This research follows a Classroom Action Research (CAR) model conducted in two cycles, with the participants being 24 male and 12 female students from class X Tav 2. Each cycle involves four stages: planning, implementation, observation, and reflection. Data collection methods include observations, tests, and documentation, which are then analyzed. The findings indicate an improvement in learning outcomes, with completion rates rising from 23% in the pre-cycle to 52% in the first cycle, and reaching 80% in the second cycle.